2017
DOI: 10.1089/met.2016.0105
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Lifestyle Characteristics and the Presence of Nonalcoholic Fatty Liver Disease: A Case–Control Study

Abstract: Higher PA level and optimal sleep duration are associated with lower likelihood, whereas sweets consumption is associated with higher likelihood of having NAFLD. These associations are independent of body weight status and energy intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 61 publications
3
43
0
Order By: Relevance
“…Greek case-control study matched with age, sex, and BMI, 30 but the results showed a tendency of protection with a OR of 0.72 (95% CI: 0.41-1.25). The possible explanation for null association is the small sample size (100 cases and 55 controls) in that study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Greek case-control study matched with age, sex, and BMI, 30 but the results showed a tendency of protection with a OR of 0.72 (95% CI: 0.41-1.25). The possible explanation for null association is the small sample size (100 cases and 55 controls) in that study.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, a study (134 cases and 217 controls) in Greece showed that nut consumption was inversely associated with NAFLD, with OR ranging from 0.92 to 0.98 . However, no association was observed between nut intake and NAFLD in another Greek case‐control study matched with age, sex, and BMI, but the results showed a tendency of protection with a OR of 0.72 (95% CI: 0.41‐1.25). The possible explanation for null association is the small sample size (100 cases and 55 controls) in that study.…”
Section: Discussionmentioning
confidence: 95%
“…Lifestyle is an important factor for metabolic syndrome, and it is associated with NAFLD [29]. Further, exercising to lose weight is an indispensable part of lifestyle interventions, and it is proposed as a useful independent item for NAFLD [22].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies have focused on assessing the role of MD, and variants of it, on the prevention and reduction of steatosis, as shown in Table 1. In a case-control study, a Mediterranean dietary and lifestyle pattern was associated to a lower likelihood of having steatosis, independently from body weight and energy intake [85]. The investigators included 100 ultrasound-proven NAFLD patients and 55 healthy controls; dietary habits were assessed through a semi-quantitative food questionnaire.…”
Section: Current Evidence About the Effects Of The Mediterranean Dietmentioning
confidence: 99%